The Effect of Return on Assets, Return on Equity, Price Earnings Ratio, Debt to Equity Ratio, and Company Size on the Stock Prices of State-Owned Companies Listed on the IDX - Septianto, Alif Fachrurrozi; Rahayu, Sri; Suryatama, Fajar (Dinasti Publisher, 2026)
This study aims to analyze the influence of Retun on Assets (ROA), Return on Equity (ROE), Price Earnings Ratio (PER), Debt to Equity Ratio (DER), and Firm Size on stock prices of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative associative approach was employed to examine the causal relationship among variables using statistical analysis through SPSS version 25. The population consists of 31 SOEs, of which 27 companies were selected as the research sample using purposive sampling based on the availability of complete annual financial reports. Secondary data were collected through documentation from financial statements, annual reports, and official IDX publications. The findings reveal that ROA, PER, DER, and Firm Size have a positive and significant influence on stock prices, indicating that operational efficiency, market expectation, sound capital structure and larger business scale receive positive responses from investors. In contrast, ROE shows no significant effect suggesting that the return on equity is not a primary consideration for investors when evaluating SOE stock performance during the study period. Simultaneously, the examined variables explain 71,1% of the variation in stock prices, while the remaining 28,9% is influenced by factors outside the research model. The study is limited by the observation period and sample scope, therefore, future research is recommended to extend the analysis period and incorporate additional variables to obtain more comprehensive results.